Penyelenggaraan Teras Baca Sebagai Solusi Guna Meingkatkan Miat Baca Anak Di Masa Pandemi Covid-19 Di Dusun Jatisari, Desa Krenceng, Kecamatan Kepung, Kabupaten Kediri - Lia Roikhanatus Sa’adah; Uzer Mustagfirin (LP3M IAIFA Kediri, 2021)
Books are one of the sources of knowledge that add insight. By reading one can find out what is in the corner of the world. This makes books often referred to as a window to the world. Book reading is also an activity that has many benefits and is well applied at the earliest possible age or the age of children. But in fact, not many children have a high interest in reading due to several factors. Especially like today where the development of technology is very fast and rapid causing all information to be easily obtained through gadgets. So that the activity of reading books began to be abandoned. The existence of the Teras Baca program aims to restore interest in reading in children, provide baha reading for them and as a place where they learn. In this study, researchers used the PAR (Participacory Action Research) method. The PAR method is one of the research models that look for something to connect the research process into the process of social change. Namely by directly holding a Teras Baca program for children. With this program, it is expected to foster interest and instill reading habits for children.